Pola Pengembangan Kurikulum Tingkat Satuan Pendidikan (KTSP) di Propinsi Sulawesi Tengah - Haeruddin Haeruddin; Patahuddin Patahuuddin; Darsikin Darsikin (Media Eksakta, 2014)
In accodance with social culture in Central Sulawesi which are various, it will need adaptive development more specially. Therefore, the problem that will be investigated in this research is: “How the system (way) development of KTSP in central Sulawesi?”. From the main problem mentioned, this study will focus on analysis to some aspects, namely: (1) How the direction of policy in implementation KTSP in central Sulawesi?, (2) How the understanding of the headmasters, teachers, schoo committee for development of KTSP?, (3) What problems faced by schools in developing KTSP?. The technique used in gaining data are: (1) Study document, (2) Observation, (3) Interview and (4) Quistionnaire. The result of research indicated local superiority that wants to be developed by Dinas Pendidikan Kota and Kabupaten are: Local Language, local arts and local handicraft. Implementation of KTSP has been implemented since 2006/2007 academic year. The headmaster’s understanding of KTSP guidebook that printed by BNSP is very low. Therefore, most of headmaster and teachers face problems in implementing KTSP. The problem is: The teachers have difficulties in developing silabus material and lesson plan in accodance local condition. The problem that is faced in developing local load is; there is no teacher who understands social culture condition in central Sulawesi. There are some suggestions recommended: The headmaster and the teachers need to be trained, to develop silabus material and lesson plan. “Pusat Kurikulum Balitbang Depdiknas” needs to socialize guidebook in developing curriculum. In developing curriculum, the member team from university should be included to participate according to their subjects.